Pengaruh Content Marketing dan Influencer Marketing Terhadap Purchase Decision pada E-Commerce Shopee di Kabupaten Pasuruan - Nur ‘Aini Salsabila (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
This study aims to analyze the influence of Content Marketing and Influencer Marketing on Purchase Decisions among Shopee e-commerce users in Pasuruan Regency. This study employs an quantitative associative approach, with data collected through questionnaires distributed to 100 active Shopee users in Pasuruan Regency, selected using purposive sampling. The data analysis technique used was multiple linear regression assisted by SPSS version 30. The results show that Content Marketing has a significant partial effect on Purchase Decisions, as does Influencer Marketing. Simultaneously, both variables have a significant influence on Purchase Decisions. These findings indicate that the use of relevant marketing content and collaboration with credible influencers can enhance consumer purchasing decisions.